The free circulation of resolutions in the EU in the case of abduction international minors (Justicia &Derecho, 2020)
This article faces the present and future regulation of the recognition and enforcement of judicial resolutions in the matter of international child abduction in the European Union. Specific subject which motivated a singular –and privileged– regime of recognition and enforcement, different from the general regime in the matter of parental responsibility. Recently, the applicable instrument, the 2201/2003 Regulation (Brussels IIa Regulation), has suffered an important recast which has ended with the promulgation of a new Regulation, the 2019/1111 Regulation. Therefore, in this work we will deal with the complex interaction between the legal sources, both of EU sources and international conventions, notably the 1980 Hague Convention, analysing not only the present regimen but also the abovementioned modifications. This analysis will allow us to conclude with some of the actual and future tendencies of the Private International Law third sector in the process of construction of a free area of freedom, security and justice in the EU.
Keywords: Recognition and enforcement of judicial resolutions; European Union; Brussels II a Regulation; Brussels II b Regulation; international child abduction